The influence of transformational leadership towards employees performance in Malaysia banking sector / Fatin Syazwani Ab. Razak - Ab. Razak, Fatin Syazwani (2019)
Leadership always plays an important role in the growth of employee performance of an organization. Performance of employee refer to the work being done by the employee include the everyday task, meeting with the deadlines and the efficient in doing work. Strong leadership is needed to encourage, motivate and influence the employee performance. In a banking sector, problem happen due to the lack of the engagement with the employee, lack of communication and lack of emotional intelligent among the employee. The problems need to be overcome by applying the element of transformational leadership which is idealized influence, individual consideration, inspirational motivation and intellectual stimulation. In collecting the data, the survey questionnaires were used. A total of one hundred thirty seven (137) were distribute in Kelana Jaya, Bank. The result shows a significant positive effect on transformational leadership towards employee performance. The findings of the study it can be conclude that there is a strong relationship between dependent and independent variable. This means, there is a positive and large relationship between idealized influence, individual consideration, inspirational motivation and intellectual stimulation and employee performance in Malaysia banking sector.